Rancang Bangun Sistem Informasi Tracking Sales dengan Integrasi Kartu Radio Frequency Identification - Mita Kharisma Permata Zion Putri; Rudi Susanto; Arif Wicaksono Septyanto (Jurnal Informatika Global)
CV. Multi Banyu Satwa is a distributor of livestock medicines and vitamins where the company sells its products to shops that sell animal needs, especially livestock. In marketing its products, this company uses a canvasing sales system where the salesperson sells for several days by directly bringing the product and will return when the goods brought have started to run out. So that there can be a risk of losing the product if the salesperson is not honest, besides that the company owner does not know the presence of the sales directly. In this regard, the purpose of this research is to build a sales canvasser tracking information system with the integration of Radio Frequency Identification (RFID) cards. The method used in building this information system uses waterfall and needs analysis using PIECES, while the system modeling design uses Unified Modeling Language (UML). This information system is web-based and there are 3 access rights, namely owner, admin, salesman. Based on the test results from testing the sales canvasser tracking information system with the integration of this RFID card using the black-box method, it can be seen that this information system can run well. Meanwhile, from the results of user testing using a questionnaire, the results showed a percentage score of 55% Agree and 45% Strongly Agree.Keywords : Information System, Tracking, Sales, RFID